2020
DOI: 10.1088/1742-6596/1446/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of problem based learning to improve student learning achievement in turning machining lesson

Abstract: The research aims to describe the application of project based learning (PBL) models to improve learning achievement, and to find an increase in learning achievement. This study uses a quantitative descriptive research approach to the type of classroom action research. The research data were obtained using an observation sheet of student learning activeness and a job grading sheet turning students. The application of PBL uses the model proposed by Carr and Kemmis where each cycle consists of four steps, planni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The findings of this study are in line with the findings of Narmaditya & Winarning (2017) who found that PBL can improve student learning achievement and problem-solving. A study by Paryanto, Hidayat, & Harjanto (2019) and by Aidoo & Boateng (2016) shows that PBL is very helpful in increasing learning achievement in terms of the capacity to debate, gather information, ask questions, and draw conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study are in line with the findings of Narmaditya & Winarning (2017) who found that PBL can improve student learning achievement and problem-solving. A study by Paryanto, Hidayat, & Harjanto (2019) and by Aidoo & Boateng (2016) shows that PBL is very helpful in increasing learning achievement in terms of the capacity to debate, gather information, ask questions, and draw conclusions.…”
Section: Introductionmentioning
confidence: 99%